THU0068 Prevalence of dyslipidaemia in an early arthritis rheumatoid cohort (ESPOIR cohort). Lack of improvement after 4 years of follow-up. (23rd January 2014) - Margerit, M.; Nguyen, P.; Pereira, B.; Allanore, Y.; Le Loët, X.; Rat, A.C.; Soubrier, M.
Abstract : Background: Cardiovascular disease accounts for about half of all deaths in RA. This excess risk is driven in part by inflammation but may be reduced by management of traditional risk factors. The recommendation of the EULAR for CV management is to assess CV risk annually with a risk equation (SCORE or Framingham equation (FRS)). A multiplier of 1.5, applied to a conventional CV risk assessment, is recommended for patients with RA with two of the following three criteria: disease duration >10 years, RF or ACPA positivity and presence of extra-articular manifestations. Crowson suggests multiplying by 1, 5 when only one criterion is fulfilled. New targets for LDL-cholesterol have been defined with SCORE equation (<70 mg/dl if SCORE >10%, <100 mg/dl if 5% ≤ SCORE<10%, <115 mg/dl if 1% < SCORE <5%). With the NCEP guidelines, LDL-C goal is <100mg/l when the FRS is >20%, <130 mg/l with >2 and <160 mg/dl with 0-1 major risk factors. A new FRS (FRS global) has been developed for a composite of all cerebrovascular events. Objectives: The aim of our study was to determine in an early arthritis rheumatoid cohort during 4-year follow-up the proportion of patients in whom the LDL-Cholesterol level was not reached. Methods: ESPOIR cohort is a nationwide, longitudinal, prospective study of 813 patients with early RA (<6 months) organized by the French Society for Rheumatology in which the patients were assessed once a year for at least 10 years. Only patients with RA according to ACR 1987 criteria aged between 40 and 65 years (age range that allows calculation of SCORE) were included in the study. Results: See Table 1 Conclusions: The percentage of patients identified as being at risk ranged significantly depending on the method. The application of a 1.5 multiplier identified more patients especially when only one factor was taken into account (ie RF or ACPA). Although rheumatologists are increasingly aware of the increase in cardiovascular risk, there was no improvement in management of lipid disorders over time. References: Crowson. Ann Rheum Dis 2011;70:719-21. Disclosure of Interest: None Declared